2012
DOI: 10.1093/brain/awr339
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted neural stem/precursor cells instruct phagocytes and reduce secondary tissue damage in the injured spinal cord

Abstract: Transplanted neural stem/precursor cells possess peculiar therapeutic plasticity and can simultaneously instruct several therapeutic mechanisms in addition to cell replacement. Here, we interrogated the therapeutic plasticity of neural stem/precursor cells after their focal implantation in the severely contused spinal cord. We injected syngeneic neural stem/precursor cells at the proximal and distal ends of the contused mouse spinal cord and analysed locomotor functions and relevant secondary pathological even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
166
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(180 citation statements)
references
References 40 publications
13
166
0
1
Order By: Relevance
“…Indeed, we found that the combination of TP and TMT led to the highest concentration of neurotrophic factors such as BDNF, NT-3, and, especially, GDNF at the epicenter region. Alternatively, the presence of more NSCs could exert more powerful modulatory effects on immune cells, leading to a greater amelioration of the secondary degenerative process (Cusimano et al, 2012). Enhanced survival should afford to provide a larger number of new neurons and oligodendrocytes derived from the NSCs to the lesioned spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we found that the combination of TP and TMT led to the highest concentration of neurotrophic factors such as BDNF, NT-3, and, especially, GDNF at the epicenter region. Alternatively, the presence of more NSCs could exert more powerful modulatory effects on immune cells, leading to a greater amelioration of the secondary degenerative process (Cusimano et al, 2012). Enhanced survival should afford to provide a larger number of new neurons and oligodendrocytes derived from the NSCs to the lesioned spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…One of the hurdles that limits the efficacy of NSCs may be inadequate survival of NSC grafts (Yu et al, 2009;Li and Lepski, 2013). Previous studies have reported a rapid decline in the number of surviving NSCs grafted into the injured spinal cord (Okada et al, 2005;Cusimano et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…4). These NPC-transplanted SCI mice show a reduction of proinflammatory M1-like macrophages at the injured site and develop much less severe secondary cord damage, compared with sham-operated controls (Cusimano et al, 2012) (Table 3).…”
Section: The Involvement Of Cellular Junctional Coupling Where Membramentioning
confidence: 95%
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%